Icariside II Restores Vascular Smooth Muscle Cell Contractile Phenotype by Enhancing the Focal Adhesion Signaling Pathway in the Rat Vascular Remodeling Model - Lv, Junyuan; Li, Xintong; Wu, Hongyu; Li, Jiayang; Luan, Boyang; Li, Yiqi; Li, Yeli; Yang, Danli; Wen, Hao (Frontiers in Pharmacology, 2022)
Vascular smooth muscle cell (VSMC) phenotypic transition represents the fundamental pathophysiological alteration in the vascular remodeling process during the initiation and progression of cardiovascular diseases. Recent studies have revealed that Icariside II (ICS-II), a flavonol glycoside derived from the traditional Chinese medicine Herba Epimedii, exhibited therapeutic effects in various cardiovascular diseases. However, the therapeutic efficacy and underlying mechanisms of ICS-II regarding VSMC phenotypic transition were unknown. In this study, we investigated the therapeutic effects of ICS-Ⅱ on vascular remodeling with a rat’s balloon injury model in vivo. The label-free proteomic analysis was further implemented to identify the differentially expressed proteins (DEPs) after ICS-II intervention. Gene ontology and the pathway enrichment analysis were performed based on DEPs. Moreover, platelet-derived growth factor (PDGF-BB)-induced primary rat VSMC was implemented to verify the restoration effects of ICS-II on the VSMC contractile phenotype. Results showed that ICS-II could effectively attenuate the vascular remodeling process, promote SMA-α protein expression, and inhibit OPN expression in vivo. The proteomic analysis identified 145 differentially expressed proteins after ICS-II intervention. Further, the bioinformatics analysis indicated that the focal adhesion signaling pathway was enriched in the ICS-II group. In vitro studies showed that ICS-II suppressed VSMC proliferation and migration, and promoted VSMC contractile phenotype by modulating the focal adhesion signaling pathway. Taken together, our results suggest that ICS-II attenuates the vascular remodeling process and restores the VSMC contractile phenotype by promoting the focal adhesion pathway.